Pengaruh Pupuk Anorganik Terhadap Pertumbuhan dan Hasil Kacang (Phaseolus radiatus L.) Varietas Vima 1 dan Vima 3 - Rahma Fikran Sujadi; Pamungkas, Djoko Heru; Maryani, Yekti (JURNAL ILMIAH AGROUST, 2023)
This study aims to determine the effect of the interaction of anorganic fertilizers on the growth and yield of green bean plants, to determine the role of anorganic fertilizers on the growth and yield of green beans varieties vima 1 and vima 3. This experiment was carried out in Parangtritis Village, Kretek, Bantul, D.I. Yogyakarta. The height of the place ± 10 m above sea level; soil pH 5.6-6.0; The average rain per year is 1400-1900 mm per year. The study was compiled in a complete group randomized design (RAKL) with two factors. The first factor of anorganic fertilizer is NPK, NP, NK, and PK. The second factor varieties green beans vima 1 and vima 3. Observation variables include plant height, number of leaves, plant fresh weight, plant dry weight, number of plant pods, plant content pod weight, plant seed weight, yield per hectare, and weight of 100 seeds. Data were analyzed using a 5% level of fingerprinting followed by Duncan's Multiple Range Test (DMRT) at a level of α = 5%. The results of the analysis showed that there were interactions in the number of pods, weight of the filled pods, and weight of seeds, the treatment of green beans of the vima 3 variety gave higher growth than the vima 1 variety, the application of NPK fertilizer gave the highest yield of green beans per hectare, and the green beans of the vima 1 variety gave better results than the vima 3 variety. Keywords: Anorganic fertilizers, varieties, growth, yield of green beans.